Biotechnology : - Ignacimuthu, S. (Alpha Science Intl Ltd, 2008)
Biotechnology: Principles and Applications covers the broad vistas of biotechnology, providing students with a sound basis of understanding various aspects of this ever-growing field. It is intended to be comprehensive and to meet the varied needs of different institutions. The book includes a wide coverage of topics needed to appreciate the principles and applied aspects of biotechnology.